2009
DOI: 10.1108/09654280911001149
|View full text |Cite
|
Sign up to set email alerts
|

What makes people decide to visit and use an internet‐delivered behavior‐change intervention?

Abstract: PurposeThe purpose of this study is to explore adults' cognitive deliberations in deciding to visit an internet intervention, to extend the visit to use and process the intervention's content, and to revisit the intervention.Design/methodology/approachA qualitative study was conducted consisting of five focus group interviews (n = 29, 25‐69 years). The interview transcriptions were subjected to systematic content analysis.FindingsThe results indicate that being motivated to change a health behavior and curiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 33 publications
(58 reference statements)
4
70
1
Order By: Relevance
“…However, other researchers suggest that Internet websites are not as effective as they should be for inducing health behavior changes (e.g., Brouwer, Oenema, Crutzen, de Nooijer, de Vries, & Brug, 2009;Cugelman, Thelwall, & Dawes, 2011). Additionally, the websites' reach for targeted segments, as well as attrition rates during the intervention are problematic (Brouwer et al, 2011;Cugelman et al, 2011).…”
mentioning
confidence: 93%
“…However, other researchers suggest that Internet websites are not as effective as they should be for inducing health behavior changes (e.g., Brouwer, Oenema, Crutzen, de Nooijer, de Vries, & Brug, 2009;Cugelman, Thelwall, & Dawes, 2011). Additionally, the websites' reach for targeted segments, as well as attrition rates during the intervention are problematic (Brouwer et al, 2011;Cugelman et al, 2011).…”
mentioning
confidence: 93%
“…In the future, we may use emails with updated information and an email and SMS reminder system [28]. Another possibility, which was considered from the outset of the design of 'MyPlan', is to implement in settings which may provide face to face support by peers or counsellors [28,29]. The basic idea is to implement MyPlan in general practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…Regularly updated content has been identified as an inducement to revisiting digital interventions [43]. To our knowledge, no other study on digital mental health interventions has identified the desire to access time-unlimited information and advice.…”
Section: The Perfect Online-interventionmentioning
confidence: 99%